2015
DOI: 10.1021/acs.jpcc.5b02276
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Energetics of Some Nonmetallic Impurity Atoms in Plutonium Dioxide

Abstract: The energetics of some typical non-metallic impurity atoms (H, Ne, Cl, Ar, Kr and Xe) in PuO 2 are calculated using a projector augmented-wave method under the framework of density functional theory. The Hubbard parameter U and van der Waals corrections are used to describe the strongly correlated electronic behavior of f electrons in Pu and weak interactions of rare gases, respectively. Three incorporation sites of for impurity atoms, i.e., octahedral interstitial, O vacancy, and Pu vacancy sites, are consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 74 publications
5
23
0
Order By: Relevance
“…An effective U (U eff = U À J; i.e., the difference between the Coulomb U and exchange J parameters, hereafter referred to as U) value of 4 eV is selected for the localized Pu 5f electrons. This value has been demonstrated by our previous calculations to be reasonable in reproducing the experimental lattice parameter, bulk modulus and band gap of PuO 2 , along with the reaction energies related to the formation of hyperstoichiometric Pu oxides [34,35]. Additionally, we test U values in the range of 3-6 eV for calculations related to PuO 2 and PuO 2.25 .…”
Section: Computational Detailssupporting
confidence: 64%
See 3 more Smart Citations
“…An effective U (U eff = U À J; i.e., the difference between the Coulomb U and exchange J parameters, hereafter referred to as U) value of 4 eV is selected for the localized Pu 5f electrons. This value has been demonstrated by our previous calculations to be reasonable in reproducing the experimental lattice parameter, bulk modulus and band gap of PuO 2 , along with the reaction energies related to the formation of hyperstoichiometric Pu oxides [34,35]. Additionally, we test U values in the range of 3-6 eV for calculations related to PuO 2 and PuO 2.25 .…”
Section: Computational Detailssupporting
confidence: 64%
“…Above all, in terms of other researchers' and our previous calculations on Pu-based materials, especially on Pu oxides [3,15,34,35,[56][57][58], we briefly discuss the general features of the electronic structures of Pu, Pu 2 O 3 and PuO 2 with or without impurity atoms. The most remarkable feature of the electronic structure of metallic Pu lies in the presence of strong localized 5f states just below the Fermi energy (E F ), indicating that the localized 5f states do not contribute to chemical bonding or hybridization with other electronic states.…”
Section: Electron Structurementioning
confidence: 96%
See 2 more Smart Citations
“…The DFT + U approach is one of the most popular methods that allow correct treatment of systems containing strongly correlated electrons. By addition of an energy term of the effective Hubbard parameter, the antiferromagnetic Mott insulator feature and structural parameters of PuO 2 are well described. Several previous studies had focused on the properties of plutonium-oxide surfaces. Jomard and Bottin investigated the influence of electronic correlations on thermodynamic stability of PuO 2 surfaces in ref and also pointed out that the electronic structure of the insulating PuO 2 surfaces can be well described within the DFT + U method, which is a prerequisite to explore chemical reactions on the PuO 2 surfaces. Sun et al further reported the effects of thickness and oxygen vacancy on the stability and chemical activity of the PuO 2 surfaces, where the spin–orbit coupling (SOC) interaction was considered .…”
Section: Introductionmentioning
confidence: 99%